They Keep It All Hid: The Ghettoization of Mental Disability Law and Its Implications for Legal Education - Perlin, Michael L. (2010)
The Supreme Court has, since 1972, decided more than fifty cases involving persons with mental disabilities, a docket spanning virtually every aspect of constitutional law and criminal procedure. These cases have dealt with the substantive and procedural limitations on the commitment power, the conditions of confinement in psychiatric institutions, the application of the Americans with Disabilities Act to persons institutionalized because of mental illness, the substantive and procedural aspects of the criminal incompetency inquiry and the insanity defense, the relationship between mental disability and sexually violent predator laws, and all aspects of the death penalty. Thousands of cases have been decided in every state in the nation dealing with similar issues. In fact, in the Supreme Court’s first modern mental disability law case – finding that the due process clause is implicated in all decisions related to both the nature and duration of the commitment process – it expressed surprise that there were not more mental disability law cases brought to its attention. However, a study of constitutional law, criminal procedure, civil rights and/or federal courts casebooks reveal virtually no mental disability law cases. Policies and practices of exclusion are not unique. By way of example, more than a decade ago, Toni Massaro pointed out that constitutional criminal procedure has been treated as a subject separate from basic constitutional law materials and courses. Mental disability law has been ghettoized in the same way that criminal procedure has been ghettoized. It is a ghettoization that in some ways is far more troubling than the criminal procedure ghettoization, since all law schools offer courses in basic criminal procedure, and these courses are regularly well-subscribed. On the other hand, there are courses in mental disability law offered only at about half of all American law schools, and, at many schools, those courses are offered infrequently and only by adjuncts (who often have no legal training). This ghettoization reflects a hard truth that has passed under the radar of most civil rights teachers and civil rights students. Mental disability law is simply not a topic taken seriously as a civil rights topic (or as a constitutional law topic or as a federal courts topic). And this failure of inclusion goes directly to the heart of the challenge of teaching mental disability law. It is hidden (nearly totally hidden) from the traditional law school curriculum. It is not in the curriculum at many law schools. It is largely invisible to students and professors alike. I believe this ghettoization is a reflection of the invidious sanism that permeates the legal academy in the same way it permeates the rest of society. Law teachers are not immune to sanism – an irrational prejudice of the same quality and character of other irrational prejudices that cause (and are reflected in) prevailing social attitudes of racism, sexism, homophobia, and ethnic bigotry. In this essay, I reconsider this ghettoization from four overlapping vantage points. First, I consider how mental disability law became a part of the law school curriculum, growing out of and largely supplanting courses in psychiatry and the law (and why this title change is not just a question of phraseology). Second, I discuss the significance of the notion that mental disability law can be cabined in one 2- or 3-credit course (implying that all mental disability law can be surveyed in that period of time, in a way that law school faculty would never think all tax law or real estate law or securities law could be so taught), and the significance of the reality that so many schools offer no course or only one course sporadically (often, without any involvement of a full-time faculty member). Third, I examine the Online Mental Disability Law program at New York Law School (where I teach) from four different perspectives: (a) the pedagogy, (b) the range of subject matters taught, (c) the interdisciplinarity of the students and the faculty, and (d) the internationality ofthe students and intersectionality of our course offerings. Finally, and most importantly, I explain why it is absolutely essential for any mental disability law course (or sequence of courses) to consider the concepts of sanism and pretextuality, the significance of ordinary common sense (OCS) and heuristic reasoning, and the impact of therapeutic jurisprudence